Free Will : art and power on Shakespeare's stage - Wilson, Richard, 1950- (Manchester University Press, 2013)
A study of theatre and sovereignty that situates Shakespeare's plays in the contraflow between two absolutisms of early modern England: the aesthetic and the political.